Contesting the Arctic : politics and imaginaries in the circumpolar North /: politics and imaginaries in the circumpolar North. (2015) - Steinberg, Philip E; Tasch, Jeremy, 1963-; Gerhardt, Hannes; Keul, Adam; Nyman, Elizabeth
No abstract available